INSTAGRAM ACCOUNT MANAGEMENT STRATEGY @ARIESSKULINER AS COMMUNICATION MEDIA IN PROMOTING CULLINARY IN PONOROGO - Salsabila, Andan Ayu (QAULAN: Journal of Islamic Communication, 2023)
Communication and information technology is increasingly sophisticated and growing rapidly. The internet is the media most widely used by the public to find everything they want to know or just for existence, one of which is social media. One of the most popular social media today is Instagram. Ponorogo Regency is one of the regencies in East Java which has a very fast culinary tour. Instagram is one of the media for promotion. Therefore, when using Instagram social media accounts, you must use a management strategy to fit the plan. This study aims to explain: (1) the strategy for managing the Instagram account @ariesskuliner in promoting culinary in Ponorgo, (2) the results of managing the Instagram account @ariesskuliner, (3) the challenges in managing Instagram @ariesskuliner. The research method used is a qualitative approach. Data collection techniques used are interviews, observation, and documentation. The data analysis used is the Miles and Huberman model. The informants in this study are the founders of the @arisskuliner account, culinary entrepreneurs, and followers. The results of this study indicate that: First, the strategy for managing the Instagram @ariesskuliner account is the planning, implementation, monitoring, evaluation stages. Second, the results obtained in managing the @ariesskuliner account are a significant increase in followers every month, and culinary entrepreneurs are very satisfied with the delivery of content that is presented in an interesting way. Third, the challenges in managing the @ariesskuliner account are finding different content, negative perceptions, and consistency in uploading content.